STUDY OF SAND RIVER AS FINE AGGREGATE IN ASPHALTIC CONCRETE WEARING COURSE (AC-WC) - Surat Surat (Jurnal Teknologi Berkelanjutan, 2014)
The asphaltic concrete wearing course (AC-WC) structure of flexible pavement must be characteristics capable of bearing the load of traffic, high durability, water-resistant, and wear-resistant as well as flat and sufficiently enough on the surface. The materials of the AC-WC consists of coarse aggregate, medium aggregate, fine aggregate, filler and with bitumen as the binder. Fine fraction aggregate of crushed stone combination with sand river. The deposit of sand river sufficient. The sand river of good quality, gradation with varying specific gravity. The crushed stone is from mountain Martadah quary and the river sand is from Awang Bangkal River, Rantau River, Pengaron River and Barito River. Research for use mountain Martadah B crushed stone material with coarse aggregate fraction proportion 18%, medium aggregate fraction 40%, fine aggregate fraction 30%, sand river 10%, filler use Portland cement 2%. River sand proportion was equalized to 10% (Awang Bangkal River or Rantau River or Pengaron River or Barito River). Combined gradation approached Fuller curve, percent of passing sieve No.100 and No.200 approaching lower limit specification for asphaltic concrete wearing course gradation. With a specific gravity greater the value, greater density of the mixture gradation, asphalt content and compaction energy the same. Density values are influenced by gradation, asphalt content, specific gravity aggregate and energy to condense. The higher density the value of VIM, VMA lower, and higher VFB. The Marshall test with immersion for 24 hours and 60°C for material crushed stone Martadah B and sand river (River Awang Bangkal or Rantau River or River Pengaron or Barito River) on mixture asphaltic concrete wearing course obtained stability Marshall value remainder is greater than 90 percent that otherwise meet the requirements.